PEMBELAJARAN BLENDED (BLENDED LEARNING) - Ibnu Ali Mas’ud; Ridha Nabilatul Lu’ayyi (Fakultas Tarbiyah IAI Almuslim Aceh, 2025)
Blended Learning is a creative educational method that integrates the benefits of face-to-face instruction with the convenience of digital technology through online learning. This approach emerged as an alternative to improve the efficiency of the learning process, provide students with easier access to materials, and adapt to each individual's learning style. In practice, Blended Learning enables more interactive interactions, both between students and instructors, and among students through various digital platforms. This article explores the basic principles of Blended Learning, its characteristics, advantages and challenges in implementation, and its relevance in today's education. It is hoped that with a deeper understanding of this learning model, educational institutions can optimize teaching strategies to improve the quality and competitiveness of education in the digital age.